2013
DOI: 10.1111/jre.12057
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between different tooth shapes and patient's periodontal phenotype

Abstract: The results of this study indicate that different tooth shapes are associated with significantly different values for the extent of the KM, its bucco-lingual thickness and the height of the interproximal maxillary central papilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 25 publications
2
44
1
2
Order By: Relevance
“…The characteristics and results of the included studies for this clinically focused question are presented in Table . All 25 included studies reported data for both KTW and GT.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics and results of the included studies for this clinically focused question are presented in Table . All 25 included studies reported data for both KTW and GT.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 studies met the inclusion criteria and provided data for this question. All studies had a cross‐sectional design.…”
Section: Focused Clinical Questionmentioning
confidence: 99%
“…Asian subjects have been reported to have thin gingival phenotype compared with Caucasian subjects . Though this suggests a population characteristic, other populations cannot be assessed because of lack of studies. There is disagreement regarding whether tooth shape predicts gingival phenotype and the role of labial plate thickness on periodontal phenotype …”
Section: Focused Clinical Questionmentioning
confidence: 99%
“…Nowadays, the periodontal biotype refers to the thickness of gingiva, bone architecture, crown morphology and the amount of keratinized tissue . The gingival thickness represents one of the important factors associated with periodontal biotype rather than a synonym for it, and it is usually classified into thick, medium and thin forms via probing into the mid‐buccal sulcus of gingiva . The underlying alveolar bone architecture is defined as flat, scalloped or pronounced scalloped, while there are no reports on its association with tooth shapes .…”
Section: Introductionmentioning
confidence: 99%